RAGS15-000-0123/The implication of goods and seryices tax operators in Malaysia - Che Mohd Salleh, Marhanum; Abdullah, Nurdianawati Irwani; Ibrahim, Khairunisah (2018)
Malaysia is reputed to be a leader in the Takaful industry within the ASEAN region commanding a market share that exceeds 70 per cent of gross Takaful contribution. The industry however is not exempted from the recent implementation of the Malaysian Goods and Services Tax (GST) in April 2015. This research project seeks to examine the specific Shari‘ah issues and challenges that may be triggered off by GST application on its operations. Other that, this research investigates the implication of GST towards the performance of Takaful operator in Malaysia even though the recent government have changed the rate of GST from 6% to 0%. Therefore, secondary data that is reliable in this research would be from 2013-2017. Accordingly, to achieve the first objective, an inductive analysis is undertaken on the relevant sources that justify GST implementation in Takaful, mainly guidelines provided by Customs Department, and also arguments from scholars on the likely contravention of Shari‘ah principles with the application of GST. Meanwhile, mixed methodology approach is adopted to observe the performance of Takaful operators during the five years period of GST which based on secondary data as well as interview sessions with Takaful representatives. After examining those supply services which are subjected to GST, the researchers conclude that the Shari‘ah issues that emerged is basically related to the contract of Takaful which is donation in nature which should not be treated similar with the conventional counterparts. In addition, Takaful riders like critical illness, medical and personal accident benefits which considered as basic needs (Dharuriyyat), shall be given tax exemption. In addition, based on Data Envelopment Analyis (DEA), The study has found that the efficiency for Takaful industry negatively impacted by the GST implementation. However, the analysis is also shown the reduction in the year 2014 compare to 2013 in the absence of GST. But compare to 2015 and 2016, the percentage of difference is in 2014 from 2013 is significantly less. This results also parallel with the results from interview sessions conducted with Takaful representatives where they reported that there are many other factors that have influenced the performance of the operators rather than the GST per say. Therefore, GST have not significantly affect the performance of the operators and the industry in general. Overall, in case of the government continue with the 6% GST rate, it is suggested to remain GST exemption on wakalah fee, fund management fee and family Takaful product. GST on Takaful is proposed to be restricted on fee & charges (ujrah based) with tax exemption on all type Tabarru’ and of all type of Takaful benefits that cater for the public needs. Hence, given that the new government have ruled with 0% GST, it is therefore grateful to the Takaful industry and the operator where their burden have been reduced. It is hope that this positive change will boost the performance of Takaful industry in the future.